2005
DOI: 10.3758/bf03196377
|View full text |Cite
|
Sign up to set email alerts
|

Does the mastery of center-embedded linguistic structures distinguish humans from nonhuman primates?

Abstract: Identifying the specific language abilities that separate humans from nonhuman primates has been the topic of innumerable speculations. In a recent Science article, Fitch and Hauser (2004; hereafter, F&H) argued that the hierarchy of grammars of increasing generative power described by Chomsky (e.g., 1957) provides the key for a response. At the lowest level of complexity are the finite state grammars (FSGs), which generate sequences by concatenating a set of elements (states) while following prespecified tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
142
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 18 publications
(9 reference statements)
3
142
8
Order By: Relevance
“…The findings in (4) lacked the appropriate controls, but later replications claim that the AABB/ABAB task, which Fitch and Hauser (4) designed to obtain evidence for recursion, can be solved by humans using a simpler strategy instead (5,9) or by a conscious counting strategy that seems unrelated to language (11). At present, there is thus no convincing demonstration of the use of recursive rules in artificial language learning in any species.…”
Section: Testing For the Use Of Other Simpler Rules To Discriminate mentioning
confidence: 91%
See 2 more Smart Citations
“…The findings in (4) lacked the appropriate controls, but later replications claim that the AABB/ABAB task, which Fitch and Hauser (4) designed to obtain evidence for recursion, can be solved by humans using a simpler strategy instead (5,9) or by a conscious counting strategy that seems unrelated to language (11). At present, there is thus no convincing demonstration of the use of recursive rules in artificial language learning in any species.…”
Section: Testing For the Use Of Other Simpler Rules To Discriminate mentioning
confidence: 91%
“…From stimuli constructed of a 1-5 and b [1][2][3][4][5] , each bird was transferred abruptly to stimuli constructed from a 6 -10 and b 6 -10 when it reached criterion performance. See Fig.…”
Section: Transfer From Five Songs Of Each Stimulus Type To Five Novelmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the discussion of the recursion-only hypothesis, concerning the narrow faculty of language (FLN, Hauser et al, 2002), has been phrased in terms of concepts derived from the Chomsky hierarchy; for example, non-regular context-free vs. right-linear regular grammars (e.g., de Vries, Monaghan, Knecht, & Zwitserlood, 2008;Fitch & Hauser, 2004;Gentner et al, 2006;Perruchet & Rey, 2005;Uddén et al, 2009). Here, we will show why the Chomsky hierarchy is irrelevant in the context of finite processing systems.…”
Section: Finiteness Of Neural Systemsmentioning
confidence: 99%
“…Likewise, Gentner, Fenn, Margoliash & Nusbaum (Gentner et al, 2006) claimed that their subjects (starlings) learnt CER using the same kind of structures as Fitch and Hauser (Fitch and Hauser, 2004). This in turn elicited some critique: Corballis (Corballis, 2007a;Corballis, 2007b) called attention to the fact that the sentences used could be parsed by simple counting, while others (De Vries et al, 2008;Perruchet and Rey, 2005) showed that in experimental situation similar to that of Fitch & Hauser (Fitch and Hauser, 2004) even human subjects used alternative strategies to solve the tasks.…”
mentioning
confidence: 99%